2015
DOI: 10.1007/s13762-015-0798-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two plant growth-promoting rhizobacteria containing 1-aminocyclopropane-1-carboxylate deaminase on oat growth in petroleum-contaminated soil

Abstract: Petroleum is potentially toxic to living organisms, and there are worldwide efforts to develop methods for bioremediation of petroleum-contaminated soils. Phytoremediation is an effective method to reduce the concentration of petroleum in soils, and plant growthpromoting rhizobacteria (PGPR) play an important role in the phytoremediation. Two PGPR, Pseudomonas aeruginosa SLC-2 and Serratia marcescens BC-3, were isolated from the rhizophere of Echinochloa grown in petroleumcontaminated soil. These isolates show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…This represents the synergistic and cumulative effect of all the strains when applied together in the agricultural production. The findings of the present study were in agreement with the study done by Pérez-Fernández and Valentine (2017), Liu et al (2015), Samaddar et al (2019) suggesting beneficial effects of consortia of PGPR is more pronounced than application of individual PGPR. Co-inoculation of microbes increases growth and yield, provides the plants with balanced nutrition and increases availability of minerals and nutrients (Manjunath et al 2011;Felici et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…This represents the synergistic and cumulative effect of all the strains when applied together in the agricultural production. The findings of the present study were in agreement with the study done by Pérez-Fernández and Valentine (2017), Liu et al (2015), Samaddar et al (2019) suggesting beneficial effects of consortia of PGPR is more pronounced than application of individual PGPR. Co-inoculation of microbes increases growth and yield, provides the plants with balanced nutrition and increases availability of minerals and nutrients (Manjunath et al 2011;Felici et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Plants being immobile means that they are confronted to various kind of stresses such as drought, flooding, salinity, heat, cold, exposure to heavy metals and nutrient deficiency, as well as phytopathogen and pests attack. The increment in synthesis of ethylene from its immediate precursor, ACC, secreted by plants as root exudates, has been found in almost all plants growing under stress conditions (Wang et al, 2013; Liu et al, 2015; Abiri et al, 2017). Ethylene is a plant hormone involved in regulation of various physiological processes of plants, but the climate change induced ethylene production in plants inflicts a significant reduction in plant growth and development and if not monitored properly could result in plant death (Iqbal et al, 2017; Dubois et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this hydrocarbon breakdown process was carried out by rhizobacteria with good emulsification activity, in addition to the fact that these enzymatic activities were stimulated by AM in the rhizosphere. These results suggested that choosing bacteria with good production of lipolysaccharides, ACC deaminase and able to synthesize siderophores, would be an effective strategy to attack recalcitrant molecules, such as petroleum hydrocarbons (Liu et al, 2015).…”
Section: Interactions In the Presence Of Abiotic Stressmentioning
confidence: 98%